Penerapan Manajemen Mutu Terpadu dalam Mendukung Akreditasi Unggul di SMKS Bina Mandiri Gorontalo - Desi Novitasari; Abdul Hamid (ALSYS, 2026)
The implementation of Total Quality Management (TQM) in vocational education plays a strategic role in improving the quality of educational services and institutional performance; however, empirical studies that specifically examine its contribution to achieving “excellent” accreditation status in vocational high schools remain limited. This study aimed to analyze the application of TQM principles and their contribution to supporting excellent accreditation at SMKS Bina Mandiri Gorontalo. A qualitative approach with a case study design was employed, involving the principal, vice principals, and teachers selected through purposive sampling. Data were collected through in-depth interviews, documentation, and observations, and were analyzed using thematic analysis. The findings show that TQM implementation at SMKS Bina Mandiri Gorontalo is reflected in visionary leadership, the involvement of all school members, continuous improvement, a strong focus on student and stakeholder satisfaction, and the quality-oriented management of facilities, infrastructure, and curriculum. These factors contribute significantly to fulfilling national education standards and to the attainment of excellent accreditation, in line with TQM theory that emphasizes a quality culture and continuous improvement in educational organizations. The study concludes that the consistent and systematic application of Total Quality Management can effectively support school quality enhancement and the achievement of excellent accreditation. The findings also carry important implications for strengthening the TQM literature in vocational education and for formulating practical recommendations for school leaders and policymakers to foster a culture of quality, enhance human resource competencies, and reinforce internal quality assurance systems.